Treatment for occult breast cancer: A propensity score analysis of the National Cancer Database - Tsai, Catherine (Am J Surg, 2019)
BACKGROUND: Controversy exists regarding optimal treatment of occult breast cancer (OBC). Treatment options include mastectomy alone (MAST), radiation alone (XRT), or mastectomy with radiation (MXRT). METHODS: We queried the National Cancer Database from 2004-2014 for patients with OBC who underwent MXRT, XRT, or MAST. We utilized propensity score matching to perform three head-to-head comparisons. Kaplan-Meier analysis was performed to compare overall survival (OS). RESULTS: A total of 190 patients received XRT, 237 received MAST, and 244 received MXRT. In the MXRT vs. XRT comparison, 5-year OS was 78.2% and 82.8%, respectively. In the MXRT vs. MAST comparison, 5-year OS was 81.5% and 86.7%, respectively. In the MAST vs XRT comparison, 5-year OS was 83.2% and 82.5%, respectively. There was no difference in OS for all paired comparisons. CONCLUSIONS: There were no OS differences in patients undergoing MAST, XRT, or MXRT, suggesting breast conservation can be considered in patients with OBC.